DESIGN METHOD DEVELOPMENT OF AXIAL HYDRO TURBINE BLADE USING CASCADE ANALYSIS - Suprayetno, Nono
The utilization of renewable energy, especially hydropower for low head applications in Indonesia, is still not optimal, while electricity demand continues to increase. Hydropower is still considered as an alternative energy to the energy generated by power plants in reducing the energy deficits. High investment costs in hydroelectric power plants hinder optimal energy utilization. However, in recent years, there have been a lot of discussion about hydropower related to the intermittence of other renewable energy plants where hydropower can operate for 24 hours with high efficiency. The rapid development of computer technology has made it easier for designers and researchers to design and plan hydroelectric power plants, especially in the design of turbine blades which are the primary movers in hydroelectric power systems. The study in the current dissertation aimed to answer these challenges through the use of computer technology. A turbine using NACA 0012 basic profile on its stator blades and NACA 0015 basic profile on its rotor blade was designed using a meridional flow analysis and cascade analysis. The stator blade was designed to have the same thickness, while the thickness of the rotor blade varies from hub to tip starts from 1 to 0,5. In addition, the coefficients of losses were investigated on some base profiles started from NACA 0010 up to NACA 0015. The viscosity effect through the application of boundary layers was implemented in the design of the turbine blade to predict the turbine performance under its actual flow condition. A coefficient in the form of a diffusion factor was given in the design process of the rotor blade to increase pressure distribution on the blade surface. Meridional flow analysis was carried out using the mixed vortex method, which was a combination of a free vortex and forced vortex criteria. Meridional flow analysis was carried out using the radial equilibrium method by controlling the tangential velocity with mixed vortex criteria which made the difference between the current turbine design in this study and the other axial hydro turbine design. Solution for meridional flow analysis was obtained from a numerical program similar to the REDES. Then, the cascade flow was analyzed using a potential flow solver and boundary layer solver. Cascade analysis was computed using the surface vorticity method or known as the vortex panel method. In addition, the vortex panel program was designed to produce pressure distribution and flow velocity on the hydrofoil surface for a boundary layer analysis. The result of the boundary layer was obtained from an approximation using an integral momentum equation. The Thwaites method was used to solve the flow in the laminar region, while the Head method solved the turbulent region. The transition from laminar to turbulent was identified by Mitchel's criterion based on changes in momentum thickness. Several boundary layer parameters such as displacement thickness ?*, momentum thickness ?, shape factor H and friction coefficient Cf were validated using a similar program for hydrofoil analysis. The vortex panel program was first converted to an hydrofoil program by modifying t/l, then compared to Pablo and XFLR5. The result shows that the accuracy of the boundary layer program in the laminar flow was very good where the transition occurs at a point close to that shown by Pablo program, while the XFLR5 separation point was slightly further downstream of the hydrofoil. This was because of the XFLR5 program was written with a different technique from the current program. The prediction results of boundary layer parameters in turbulent flow showed a slight difference between the Author’s program with Pablo and XFLR5 but it was still quite good and reasonable. Furthermore, drag coefficient of cascade blade was higher than that single hydrofoil blade calculated at the same inlet angle. The cascade flow analysis with considering boundary layer was extended to various hydrofoil profiles with several variations of pitch chord ratio and outlet angle. The panel method was used to obtain the aerodynamic forces required in blade design more shortly. It also gave easier identification of energy losses in the hydrofoil cascade. The computation shows that the loss coefficient of hydrofoil cascade will increase when the camber angle was increased due to the pressure gradient and the separation flow in the high camber. Researchers could use the diagram to predict lift and loss coefficient more easily based on the parameter of the cascade blade that has been obtained. Turbine simulations were also carried out using Ansys Fluent. A turbine was designed based on parameters obtained from the previous analysis. The diffusion factor coefficient given to the turbine was 0.019 and applied to eleven turbine blade segments. The turbine was consists of 12 stator blades and five rotor blades. The simulation results showed that the average of maximum turbine was higher than 88% at various flow rates and rotational speeds. However, the efficiency on the design point reached 85,53%. Visual observation on the blade showed that the runner has a large pitch that causing losses due to the condition. Nevertheless, the overall simulation results show a reasonable number of turbine performances. A prototype of the turbine was constructed as a testing model to obtain actual turbine performance through experiments. A turbine was designed using a permanent magnet generator mounted on both the tip of the turbine blade and shroud, which is known as Hydro Turbine with Permanent Magnet Generator (TAGMP). A turbine was designed in a compact form to reduce losses, such as mechanical losses and others. However, the operating point (design point) was not obtained when conducting the TAGMP test's performance because an anomaly occurred in the generator. It caused the generator body to heat up and reduce the generator's performance. Therefore, a similarity analysis was conducted to determine the turbine performance based on the results of field tests. Based on the analysis, the turbine efficiency was 81.86%. Based on the results, the efficiency of the nonviscous analysis reached 88,89%, the boundary layer analysis gained 82,93%, while efficiency for numerical simulation and experimental results reached 85,53% and 81,86%, respectively. Nevertheless, it could be concluded that the method of turbine blade design using cascade analysis and boundary layer could be used in the design of axial hydro turbines. Virtual testing shows that turbines can convert energy from water into mechanical energy with high efficiency. In addition, a prototype of the developed turbine in compact form could reduce mechanical losses and investment costs. Therefore, TAGMP is expected to be one of the solutions to energy problems in Indonesia. An abundance of renewable energy potential could encourage the emergence of ideas for developing a creative economy based on renewable energy, especially hydropower, for the people’s prosperity and national energy security.